Determination of Correlation of Body Mass Index and Waist Hip Ratio with Cardiovascular Parameters in Sedentary Males - Jayalakshmi, M. K. (New Frontiers in Medicine and Medical Research Vol. 5, 2021)
Background: There is an excess of adipose tissue accumulation in obesity which is associated with more sympathetic activity resulting major potential mechanism contributing to increased risk of cardiovascular complications. Obesity is associated with coronary arterial diseases, type-2 diabetes mellitus, infertility, osteoarthritis, and colo-rectal cancers. Visceral fat is more atherogenic. Methods: 100 sedentary healthy male subjects selected randomly in the general population of Davangere city. Anthropometric parameters like weight, height, waist and hip circumference were measured. With these, Body Mass Index (BMI), Waist Hip Ratio (WHR) were calculated. Correlation between BMI and WHR with cardiovascular parameters was made. Objectives: To determine body mass index, waist hip ratio and cardiovascular parameters in sedentar Subjects. To correlate body mass index, waist hip ratio with cardiovascular parameters in sedentary Subjects. Results: There was statistically significant increase in body mass index, waist hip ratio, blood pressure and pulse rate was seen and there was positive correlation between body mass index, waist hip ratio with blood pressure and pulse rate in sedentary subjects. Conclusion: Sedentary life style and obesity are associated with increase in body mass index, waist hip ratio, blood pressure and pulse rate. There is a positive correlation between Body Mass Index, Waist Hip Ratio with Pulse Rate, Systolic and Diastolic Blood Pressure.